The personal and professional importance of post-registration postgraduate education - Walker, Louise; Spendlove, Zooey (Mark Allen Healthcare, 2018)
The nature of both pre-registration and post-registration midwifery education has changed dramatically over the last two decades, being firmly established within academia and the higher education domain. Notwithstanding the changes to midwifery education, midwives' perceptions of post-registration education, and continual professional development in particular, are mixed. The terms professional training and post-registration education are used interchangeably despite representing different goals. This article will explore professional perceptions of the post-registration educational journey, the concept of further academic development for individual midwives through postgraduate study and how engagement of midwives in postgraduate study could benefit both individual midwives and the collective profession of midwifery.